(untitled) (Eurasian Journal of Ecology, 2025)
Сurrently the genetic studies of dogs are carried out quite widely. However, there are more than 400 varieties and breeds of dogs in the world, and not all of them are equally well studied. Thus, the genetical characteristics of mastiff dogs, which include the Kazakh national breed of herding dogs Tobet, have not been sufficiently studied. The purpose of this work is to review the genetic studies available in the scientific literature in varieties of mastiff-like dogs. The review examines the genetic diversity of mastiff dogs, the mechanisms of adaptation of breeds to living conditions, genetic factors of predisposition to diseases, as well as phylogenetic relationships between different breeds. Revealing phylogenetic connections of aboriginal dog breeds allows us to trace the correlation with the history and phylogeography of the peoples who inhabited the areas where these breeds were formed. Analysis of the parameters of genetic diversity and the level of inbreeding will allow us to apply science-based approaches to preserve and improve national dog breeds. Genetic research will improve breeding programs, reduce the number of hereditary diseases in dogs, help preserve the gene pool of the breed, as well as restore local breeds, including Tobets, which are on the verge of extinction. Keywords: mastiff dog breeds, Tobet, genetic diversity, phylogeny